Investigations into interplay mechanism between inter-area and local oscillatory modes in a power system - Tan K.K.; Mukerjee R.N. (2023)
Low frequency inter-area oscillations are inherent in interconnected power systems. Satisfactory damping of power oscillations is an important issue to be addressed when dealing with the rotor angle stability of power systems. Inter-area modes are caused by two or more groups of closely coupled machines interconnected by weak ties. Local modes of oscillations are localized at one station or a small part of the power system. The paper investigates into the phenomenon of the local modes becoming unstable, while attempting to suppress the inter-area mode, posing difficulty in PSS tuning. Behaviour of synchronous machines Vis a Vis weakly coupled interconnected power systems is reviewed to explain the interplay between these two mode types.